1997
DOI: 10.1007/s002340050402
|View full text |Cite
|
Sign up to set email alerts
|

Fast FLAIR of the brain: the range of appearances in normal subjects and its application to quantification of white-matter disease

Abstract: Axial fast FLAIR images of the brains of 40 normal volunteers in four age groups between 16 and 55 years were examined and the number and size of areas of increased white-matter signal recorded. Increased signal in the corticospinal tract region was seen at the level of the internal capsule in all subjects, extending up towards the centrum semiovale and down towards the pons for 0.5-5.5 cm (median 2.5 cm). In all cases the IIIrd and IVth ventricles were outlined by a thin line of high signal. Focal areas of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…Our results indicate that 3D FLAIR images delineated white matter tracts with higher contrast than 2D FLAIR images and 2D T2WI. Gawne-Cain et al 9 reported that an increased signal intensity was seen in the CST in healthy volunteers on fast FLAIR images at 1.5T MR imaging. In our study, the CST exhibited the highest contrast on 3D FLAIR compared with 2D FLAIR images and 2D T2WI.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that 3D FLAIR images delineated white matter tracts with higher contrast than 2D FLAIR images and 2D T2WI. Gawne-Cain et al 9 reported that an increased signal intensity was seen in the CST in healthy volunteers on fast FLAIR images at 1.5T MR imaging. In our study, the CST exhibited the highest contrast on 3D FLAIR compared with 2D FLAIR images and 2D T2WI.…”
Section: Discussionmentioning
confidence: 99%
“…12 Such lesions are thought to reflect foci of ischemia or infarction which arise because of microangiopathic disease. 13 This study suggests that 7T T 2 * imaging could facilitate the differentiation between MS lesions and small ichaemic WM lesions by demonstrating differences in their vascular anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, periependymal white matter hyperintensity volume was reproducible, but count less so. Pulsation of ventricular cerebrospinal fluid and subject motion may cause artifacts, with partial volume averaging impeding accurate segmentation of small (<1 cm 3 ) periependymal lesions (De Coene et al., 1992; Gawne‐Cain, Silver, Moseley, & Miller, 1997; Kates, Atkinson, & Brant‐Zawadzki, 1996). Subcortical lesions are unaffected by cerebral spinal fluid (CSF) pulsation artifacts and had higher ICC.…”
Section: Discussionmentioning
confidence: 99%